Antibacterial Activity of Silver-Modified CuO Nanoparticle-Coated Masks - Tanuja Udawant; Prajkta Thorat; Payal Thapa; Manali Patel; Saroj Shekhawat; Roshni Patel; Ankit Sudhir; Om Hudka; Indra Neel Pulidindi; Archana Deokar (Bioengineering)
A green and cost-effective sonochemical synthetic method was followed for coating silver-modified copper oxide (Ag-CuO) nanoparticles (NPs) on disposable surgical mask. The NP-coated masks were systematically characterized using XRD and FT-IR for understanding the structural and surface functionalities. In addition, the field emission scanning electron microscopy (FE-SEM) analysis showed the homogeneous coating of Ag-CuO NPs over the mask fibers. The average particle size of Ag-CuO was found to be ~70 nm. The NP-coated masks are useful to combat a broad range of bacterial species by taking the unique advantage of the synergistic effect of Ag and metal oxide (CuO and ZnO) NPs for the generation of reactive oxygen species (ROS). Zone of inhibition (ZoI) studies demonstrated antibacterial activity against both Gram-positive S. aureus and Gram-negative E. coli bacteria, probably due to the elevated production of ROS by the defect structure of the Ag-modified metal oxide NPs. The material was found to be effective against both airborne and soil-borne bacteria. We repeat that this paper deals only with the killing effect of the nanoparticles (Ag-modified CuO) on bacteria, and no studies on viral species are performed.